2013
DOI: 10.1002/jgrb.50389
|View full text |Cite
|
Sign up to set email alerts
|

Inversion for absolute deviatoric crustal stress using focal mechanisms and coseismic stress changes: The 2011 M9 Tohoku‐oki, Japan, earthquake

Abstract: [1] The absolute magnitude of stress in the crust and the shear strength of faults are poorly known, yet fundamental quantities, in lithospheric dynamics. While stress magnitude cannot be measured directly, deviatoric stress state can be inferred indirectly from focal mechanism solutions collected before and after an earthquake. We extend a standard stress inversion for normalized stresses to invert for the 3-D spatial distribution of absolute deviatoric stress and variation of fault strength with depth using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 83 publications
4
30
0
Order By: Relevance
“…The difference in orientations may indicate that the stress in the earthquake zone was decreased to a low level during the coseismic rupture, which is consistent with one seismicity analysis for this event (Görgün, 2013). If the focal mechanisms of a number of earthquakes before the mainshock can be collected, it would be possible to estimate deviatoric stress in the earthquake zone, as has been done for the 2011 Tohoku-Oki, Japan earthquake (Yang et al, 2013b). However, this analysis is far beyond what is possible using only InSAR-determined slip models.…”
Section: Mechanical Implications Of the Slip Modelssupporting
confidence: 72%
“…The difference in orientations may indicate that the stress in the earthquake zone was decreased to a low level during the coseismic rupture, which is consistent with one seismicity analysis for this event (Görgün, 2013). If the focal mechanisms of a number of earthquakes before the mainshock can be collected, it would be possible to estimate deviatoric stress in the earthquake zone, as has been done for the 2011 Tohoku-Oki, Japan earthquake (Yang et al, 2013b). However, this analysis is far beyond what is possible using only InSAR-determined slip models.…”
Section: Mechanical Implications Of the Slip Modelssupporting
confidence: 72%
“…In particular, rotations of inferred major compressive stress axes have been documented for the co-seismic effect near the fault zone of the Tohoku-oki event (Hasegawa et al, 2011;Hardebeck, 2012), and have been used in joint stress inversions (Yang et al, 2013). These studies suggested near-complete shear stress drop along the fault due to the M9, indicating ∼ 10 MPa pre-earthquake deviatoric stress levels close to the fault interface Hardebeck, 2012), and closer to ∼ 50 MPa in the upper crust (Yang et al, 2013). Yoshida et al (2012) studied the change in seismicity in the northern Honshu area before and right after the M9 and compared results with estimates from coseismic stress modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical inversion (Wesson and Boyd 2007;Yoshida et al 2012;Yang et al 2013) or forward modeling (e.g., Yoshida et al 2014Yoshida et al , 2015 can then be used to determine the background differential stress. This approach requires spatially mapping the stress rotation with a resolution that may not be possible for smaller or more poorly recorded events.…”
Section: Discussionmentioning
confidence: 99%
“…Rotations of the principal stress axes have been observed following recent great subduction zone earthquakes (e.g., Hasegawa et al 2011Hasegawa et al , 2012Hardebeck 2012;Chiba et al 2012;Yang et al 2013). These rotations usually take the form of a change in the plunge of the maximum compressive stress axis, σ1, and can also involve a horizontal rotation of the trend of the sub-horizontal σ1 axis.…”
Section: Introductionmentioning
confidence: 99%